Diagnostic accuracy of serological tests for the diagnosis of Chikungunya virus infection : A systematic review and meta-analysis - Anna, Andrew; Tholasi Nadhan, Navien; Tzi, Shien Yeoh; Marimuthu, Citartan; Ernest, Mangantig; Magdline Sia, Henry Sum; Ewe Seng, Ch'ng; Thean-Hock, Tang (PLOS, 2022)
Chikungunya virus (CHIKV) causes febrile illnesses and has always been misdiagnosed as other viral infections, such as dengue and Zika; thus, a laboratory test is needed. Serological tests are commonly used to diagnose CHIKV infection, but their accuracy is questionable due to varying degrees of reported sensitivities and specificities. Herein, we conducted a systematic review and meta-analysis to evaluate the diagnostic accuracy of serological tests currently available for CHIKV.